TANGGUNG JAWAB PENGEMBANG (DEVELOPER) DALAM PENJUALAN SATUAN UNIT APARTEMEN TERKAIT KETIADAAN IZIN MENDIRIKAN BANGUNAN (STUDI KASUS APARTEMEN 45 ANTASARI JAKARTA SELATAN) - Riza Mediana Fitri; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2019)
In the sale of apartment, developer can carry out marketing before the construction are done or commonly called Pre Project Selling system, the selling and buying must be written in the form of Sales and Purchase Agreement. To do sales by pre project selling, developer must to fulfill administrative requirements, one of which is Building Permits. Moreover, because the selling and buying must be written in the form of Sales and Purchase Agreement, one of requirements to get Sales and Purchase Agreement is to have building permits. In the construction of apartment developers also must have building permits of apartment which is given from regional government. But in reality, there are still project of apartement construction doesn’t have building permits, for example 45 Antasari Apartment. Building permits are necessary to ensure legal certainty of a building. Therefore, responsibility of developer is necessary if he neglect one’s duties. By analysis the author suggest the responsibilities of developer can be interpreted more, which will be further analysis using the normative legal research by examining primary and secondary legal materials that have been collected and processed for the formulation of research conclusions.